2015
DOI: 10.1002/jmri.25007
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient (ADC) measurements in pancreatic adenocarcinoma: A preliminary study of the effect of region of interest on ADC values and interobserver variability

Abstract: The ROI method had a considerable influence on both the minimum and mean ADC values and the interobserver variability in PDAC. The worst interobserver variability was observed for both the minimum and mean ADCs derived from small solid-sample ROI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 39 publications
2
48
0
2
Order By: Relevance
“…Larger ROIs [142] and volumetric ROIs [34] demonstrated better reproducibility. Smaller ROIs are also known to suffer from poorer inter-and intra-observer variability [153] . ADC cut-off values are increasingly used in studies to differentiate between normal and cancerous tissues or even between tumour grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger ROIs [142] and volumetric ROIs [34] demonstrated better reproducibility. Smaller ROIs are also known to suffer from poorer inter-and intra-observer variability [153] . ADC cut-off values are increasingly used in studies to differentiate between normal and cancerous tissues or even between tumour grades.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Siemens Sonata Ma et al [153] , 2015 Table 4 Estimates of apparent diffusion coefficient values reported in human pancreatic body using a mono-exponential fit Some studies were carried out with more b-values than specified in the following table to compute intravoxel incoherent motion-specific parameters. Jafar MM et al .…”
Section: Prostatementioning
confidence: 99%
“…During clinical usage, ROI RDSS was the most commonly used ROI selection method for measuring the ADC values. Previous studies indicated that since the ROI RDSS was commonly placed on the area where the tumor showed relative higher signal intensity on DW images, ROI RDSS tended to reflect the most solid, cellular or viable portion of the tumor (1120). However, our study results indicated that inter-reader variability was an major limitation of ROI RDSS .…”
Section: Discussionmentioning
confidence: 99%
“…Previous DWI related studies have mainly utilized three kinds of ROI selection methods to obtain ADC values, including whole tumor ROI, single slice ROI, and reader-defined small sample ROI in selected slices (11). ROI on single or selected slice may lead to inter-reader variability, and does not reflect the tissue heterogeneity (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation